Undergraduate students' performances in linear algebra: factorization of a determinant of n*n dimensional matrices - Ozdag, Hulya; Aygor, Nilgun (ELSEVIER SCIENCE BV, 2012)
The purpose of this study was to investigate the undergraduate students' performance and the methods to find the factorization of a determinant of n*n dimensional matrix. The participants were seventy-one undergraduate mathematics students from Yildiz Technical University. The study was qualitative in nature. The participants were asked to find the factorization of determinant of given matrix. The data was analyzed by researchers jointly. Four different methods were used by students. These methods could be categorized as traditional and non-traditional methods. Along with the abstract form of the matrices and the dimension of matrices were identified as main factors for students to use different approaches but the dimension of a matrix affects the students' performance negatively. (C) 2012 Published by Elsevier Ltd. Selection and/or peer review under responsibility of Prof. Dr. Huseyin Uzunboylu
Keywords: Linear algebra; teaching linear algebra; factorization of determinant of matrix; Education & Educational Research